2020
DOI: 10.2196/18796
|View full text |Cite
|
Sign up to set email alerts
|

Public Engagement and Government Responsiveness in the Communications About COVID-19 During the Early Epidemic Stage in China: Infodemiology Study on Social Media Data

Abstract: Background Effective risk communication about the outbreak of a newly emerging infectious disease in the early stage is critical for managing public anxiety and promoting behavioral compliance. China has experienced the unprecedented epidemic of the coronavirus disease (COVID-19) in an era when social media has fundamentally transformed information production and consumption patterns. Objective This study examined public engagement and government respon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
180
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(189 citation statements)
references
References 43 publications
5
180
0
4
Order By: Relevance
“…In China, online users generally had low engagement with posts relevant to COVID-19 from government agencies. Public posts that attracted more engagement, were more personal, showed empathy to affected people, and expressed worry about the epidemic [40]. Merely sharing updated information and policies may be insufficient to capture public interest in official communications.…”
Section: What Else Can Be Done: Recommendationsmentioning
confidence: 99%
“…In China, online users generally had low engagement with posts relevant to COVID-19 from government agencies. Public posts that attracted more engagement, were more personal, showed empathy to affected people, and expressed worry about the epidemic [40]. Merely sharing updated information and policies may be insufficient to capture public interest in official communications.…”
Section: What Else Can Be Done: Recommendationsmentioning
confidence: 99%
“…Negative emotions are more common in social media than news sites and blogs [53], because the public health crisis information on social media is usually constructed in an emotional way [54], which is more likely to evoke personal emotions through a vivid dramatic description of the risk. A recent study shows that the mainstream media in China mainly emphasize information about instrumental support and praise people or organizations, while the information which shows empathy to affected people, blames other individuals or government, and expresses worry about the pandemic is more active in the discussion taking place in social media during the early pandemic stage in the Chinese mainland [55]. Although discrete emotions have different roles in the formation of perceptual and behavioral outcomes [56], studies have shown that both fear and anxiety can encourage individuals to avoid or prevent a particular threat, thus prompting them to seek information that may be relevant to protective measures against the threat [57].…”
Section: Negative Emotionsmentioning
confidence: 99%
“…Engagement with social media posts represents different levels and are calculated differently. Popularity is calculated through number of likes per post; commitment through number of comments and virality through number of shares with the latter representing the highest behavioural level (Kim & Yang, 2017;Liao et al, 2020). Moreover, professions that were not included in the image and were reported in the comments were divided into three categories: healthcare, nonhealthcare professionals and another group that possibly span both.…”
Section: Data Extraction and Codingmentioning
confidence: 99%